Quaternary functionalized mesoporous adsorbents for ultra-high kinetics of CO2 capture from air - Tao Wang (Nature Portfolio, 2020)
Abstract Obstacles to widespread deployments of direct air capture of CO2 (DAC) lie in high material and energy costs. By grafting quaternary ammonium (QA) functional group to mesoporous polymers with high surface area, a unique DAC adsorbent with moisture swing adsorption (MSA) ability and ultra-high kinetics was developed in this work. Functionalization is designed for efficient delivery of QA group through mesopores to active substitution sites. This achieved ultra-high kinetics adsorbent with half time of 2.9 min under atmospheric environment, is the highest kinetics value reported among DAC adsorbents. A cyclic adsorption capacity of 0.26 mmol g−1 is obtained during MSA process. Through adsorption thermodynamics, it is revealed that adsorbent with uniform cylindrical pore structure has higher functional group efficiency and CO2 capacity. Pore structure can also tune the MSA ability of adsorbent through capillary condensation of water inside its mesopores. The successful functionalization of mesoporous polymers with superb CO2 adsorption kinetics opens the door to facilitate DAC adsorbents for large-scale carbon capture deployments.